JAINJ's procedure in overcoming heresy in the state of Johor - Syaimak Ismail; Mahasin Mearaj@Saja; Siti Noor Ain Aziz
The role of Jabatan Agama Islam Negeri Johor (JAINJ) is seen as very important in maintaining the faith and belief of Muslims in Johor. Muslims have an obligation to preserve the creed to avoid chaos, division, and fighting among Muslims simply because of differences in beliefs and beliefs. In fact, JAINJ's efforts to preserve the ideology and beliefs of the Johor Muslim community began in 1862 and continues until now. Accordingly, JAINJ's governance structure will always change based on suitability and specific situations. The focus of this study will be on the governance of JAINJ in dealing with the problem of heresy in this state. The governance of JAINJ under the Syariah Belief Unit in dealing with the issue of heresy and unaccepted teachings in the state of Johor will be examined in depth in this study. This study will identify the types of heresy that are most often spread in the state of Johor, besides to discover the successfulness of JAINJ in overcoming the heresy. The interview method was used to obtain information about the work done by JAINJ officers. However, this study also focuses on document analysis to get answers to the outlined objectives. According to the findings, JAINJ plays an important role in dealing with the spread of heresy in Johor and it has a systematic management system to combat the problem of heresy.